Comprehensive Assessment Of The Spread Of Echinococcosis And Improvement Of Preventive Measures (Texas Journal of Medical Science, 2025)
The annual incidence in Uzbekistan and Tajikistan is estimated at 25-27 cases per 100 000 population. The data obtained confirm that the Fergana region is a region with persistent echinococcosis circulation, where the actual prevalence may be higher than the official surgical incidence. We conducted a retrospective statistical analysis of echinococcosis incidence in the Fergana region for the period 2023-2024. The overall incidence dynamics show 19 cases in 2023 and 20 cases in 2024, an increase of +5.3%. Thus, the overall incidence of echinococcosis in the region remained relatively stable, with a slight increase compared to the previous year. Specific control and preventive measures adapted to regional conditions are proposed